Association between the serum uric acid to HDL cholesterol ratio and forearm bone mineral density in middle-aged and older adults - Song, Fangping; Sang, Yao; Fang, Xiuyan; Tang, Zilong; Zhang, Ling (Frontiers in Endocrinology, 2026)
BackgroundOsteoporosis has emerged as a growing public health concern due to its high prevalence and substantial economic burden on both individuals and society. Recent studies have identified the serum uric acid to high-density lipoprotein cholesterol ratio (UHR) as a novel predictive biomarker for various diseases. However, its association with bone mineral density (BMD) remains unclear.ObjectiveThis study evaluated the association of the UHR and forearm BMD (FR-BMD) in a middle-aged and elderly cohort. We also assessed the interaction effects of age, sex, and body mass index (BMI).MethodsA total of 4,958 adults aged ≥50 years were enrolled from health examinees at Heze Municipal Hospital (2022–2025). We collected demographic data, serum lipids, and uric acid levels. Measurements of FR-BMD were performed on the left distal radius (1/3 site) utilizing dual-energy X-ray absorptiometry. Multivariate linear regression analyses evaluated the UHR-BMD relationship, supplemented by subgroup analyses and interaction tests. Nonlinear associations were assessed using generalized additive models with smoothing curves.ResultsAfter adjusting for age, sex, BMI, Alb, ALP, ALT, BUN, TP, Scr, Lp(a), TC, GGT and hypertension, a higher UHR was significantly associated with lower FR-BMD [β=-0.076, 95%CI(-0.138~-0.015), P = 0.015]. Significant interaction effects were observed for age and sex (P for interaction < 0.05). Subgroup analysis revealed that this inverse association was significant in males and overweight individuals (P < 0.05). In contrast, a positive association was observed in females aged ≥ 60 years [β = 0.278, 95%CI(0.126~0.430), P<0.001]. Nonlinear analyses demonstrated a U-shaped relationship in those with BMI < 24 kg/m² (inflection point: 0. 102), an inverted U-shaped association in females ≥60 years (inflection point: 0. 156) and a significant but nonspecific nonlinear association was observed in males aged <60 years.ConclusionThe association of UHR with FR-BMD is significantly modified by age and sex in middle-aged and elderly populations. Nonlinear relationships exist in males <60 years, females ≥60 years and non-overweight individuals. The potential of UHR as a novel indicator for bone health assessment in select populations is highlighted by our results.